Aplikasi biomaterial aktif dari daging ikan gabus (Channa striata) untuk penyembuhan luka pascaoperasi pada hewan model tikus Wistar - Sunarno Sunarno; Rahayu Damayanti; Alfisa Devi; Muhammad Fikri; F Pratiwi; Linda Ayu (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
One problem for postoperative patients is tissue recovery takes a long time due to the occurrence of blood clotting disorders and immune system. Snakehead fish was known to contain bioactive ingredients that can potentially speed up the process of tissue repair as a result of injuries. Snakehead fish meat contains a lot of minerals, albumin, and amino acids needed for tissue protein synthesis and increases the antioxidant glutathione. This study was conducted to test the extraction of snakehead fish flesh against skin tissue wound healing in Wistar rats. The study was conducted with a completely randomized design consisting of three treatments with 6 replication, which include (P0) a negative control (without treatment madecassol and snakehead fish meat extract), (P1) madecassol commercial drug treatment, and (P2) treatment of snakehead fish meat extract. Each material was injected intramuscularly in Wistar rats at a dose of 9 ml/kg bb for 7 days. Data analysis uses Anova followed by test Honestly Significant Difference (HSD) with a significance of 95%. Treatment of snakehead meat extract with a dose of 9 ml/kg bb a significant effect on skin tissue repair after injury, better than treatment with madecassol and control with the average value of extensive tissue remaining after recovering from the condition of the wound by 0.2 cm2; 0.33 cm2; and 0.4 cm2, respectively. Snakehead fish meat extract with a dose of 9 ml/kg bb injected intramuscularly can accelerate the recovery of tissue in the skin after the wound in Wistar rats.